DESAIN EKSPERIMEN UNTUK PENGEMBANGAN FORMULA NANOKOMPOSIT RIFAMPISIN DENGAN PEMBAWA LIPID STEARIL ALKOHOL - Istiqomah, Nurani
Latent tuberculosis is caused by Mycobacterium tuberculosis (Mtb) that persist within macrophages. The delivery of antituberculosis drugs to reach Mtb within macrophages is challenging due to low internalization of the substances. The aim of this research is to determine the optimum formula for nanostructured lipid carrier (NLC) containing rifampicin that was surface modified with macrophage targeting agent, mannose, to mimic Mtb entry to macrophages. This system is called nanocomposite. D-mannose was conjugated with chitosan using an amine reducing agent, sodium triacetoxyborohydride. Conjugation of mannose with chitosan which could enclose the NLC, make mannose attached to NLC. The conjugate was characterized by FTIR spectrophotometry and its FTIR spectrum showed wavelength number changes at amide band and also Schiff base formation. The nanocomposite was prepared by emulsifying the oil phase consisted of stearyl alcohol, oleic acid and rifampicin, with aqueous solution of Tween®80 and chitosanmannose conjugate. Subsequently, particle solidification was done by ionotropic gelation using STPP. The formula was optimized by fractional factorial (FFD) and Box-behnken designs by selecting significant factors. The selected factors of FFD were rifampicin, lipid, Tween®80, conjugate, and STPP at 2 level concentrations. Meanwhile, the Box-behnken design consisted the factors of lipid, Tween®80, and conjugate. Both designs analyzed responses of particle size, encapsulation efficiency and drug loading. The optimum nanocomposite had particle diameter of 766.1 ± 57.56 nm with polydispersity index of 0.32 ± 0.02, zeta potential of ????3.20 ± 1.75 mV, encapsulation efficiency of 91.54 ± 0.18% dan drug loading of 36.62 ± 0.07%. The profile of rifampicin release was similar both at pH 5.2 and 7.4. This rifampicin nanocomposite formulation is potential to be developed for targeting the persistent Mtb in macrophages.